Design and Simulation of a Decentralized Railway Traffic Control System - Kara, T.; Cengiz Savas, M. (Engineering, Technology & Applied Science Research, 2016)
With the increasing use of railway transportation, various methods have been developed for the control and management of train traffic. Train traffic control systems that are currently in use are overwhelmingly centralized systems. In this study, the development of the general structure of railway traffic control techniques is examined, centralized and decentralized control systems are investigated, and an alternative train traffic control system, the Decentralized Train Traffic Management System (DTMS), is suggested. Simulation results on the possible application of the proposed method to a railway line in South-East Turkey are employed to evaluate the performance of the developed system.